A Comprehensive Review on Solid LIPID Nanocarriers for Enhanced Bioavailability of Poorly Soluble Anticancer Drugs - Mahesh Tanguturi, (Asian Journal of Pharmaceutics (AJP), 2025)
Acalabrutinib and sunitinib, potent anticancer agents, face significant challenges in clinical use due to their poor solubility, limited bioavailability, and off-target toxicity. Solid lipid nanocarriers (SLNs) have emerged as a versatile drug delivery platform capable of addressing these limitations. SLNs offer advantages such as improved solubility, protection against enzymatic degradation, controlled drug release, and targeted delivery, making them ideal for enhancing the therapeutic potential of these drugs. This review explores the formulation strategies, mechanisms of bioavailability enhancement, and recent advancements in SLN technology for the delivery of acalabrutinib and sunitinib. Key topics include the role of SLNs in improving drug absorption, overcoming firstpass metabolism, and achieving tumor-specific targeting. Emerging trends such as functionalized SLNs, hybrid nanocarriers, and stimuli-responsive systems are highlighted, showcasing their potential for precision oncology. While SLNs demonstrate promising results in preclinical studies, challenges such as scalability, long-term stability, and regulatory hurdles must be addressed for successful clinical translation. This review provides a comprehensive overview of SLNs as a transformative approach for enhancing the bioavailability of acalabrutinib and sunitinib, emphasizing their potential to revolutionize cancer therapy through innovative drug delivery solutions.